Pravastatin-induced proangiogenic effects depend upon extracellular FGF-2 - Shiota, Masayuki (Blackwell Publishing Ltd, 2012)
The HMG-CoA reductase inhibitors (statins) have been shown to exert several protective effects on the vasculature that are unrelated to changes in the cholesterol profile, and to induce angiogenesis. The proangiogenic effect exerted by statins has been attributed to the activation of the PI3K/Akt pathway in endothelial cells; however, it is unclear how statins activate this pathway. Pravastatin-mediated activation of Akt and MAPK occurs rapidly (within 10 min.) and at low doses (10 nM). Here, we hypothesized that FGF-2 contributes to the proangiogenic effect of statins. We found that pravastatin, a hydrophilic statin, induced phosphorylation of the FGF receptor (FGFR) in human umbilical vein endothelial cells. SU5402, an inhibitor of FGFR, abolished pravastatin-induced PI3K/Akt and MAPK activity. Likewise, anti-FGF-2 function-blocking antibodies inhibited Akt and MAPK activity. Moreover, depletion of extracellular FGF-2 by heparin prevented pravastatin-induced phosphorylation of Akt and MAPK. Treatment with FGF-2 antibody inhibited pravastatin-enhanced endothelial cell proliferation, migration and tube formation. These observations indicate that pravastatin exerts proangiogenic effects in endothelial cells depending upon the extracellular FGF-2.